2022
DOI: 10.3390/jrfm15080365
|View full text |Cite
|
Sign up to set email alerts
|

Hedging Policies to Reduce Agency Costs in Brazil

Abstract: Given the recent Brazilian economic scenario, characterized by political uncertainties and economic instabilities, it is essential for companies to engage in hedging as part of their financial policy in order to prevent their results from being affected by market frictions. In this context, the present study aimed to verify the impact of hedging on the agency costs of Brazilian companies. The methodology used was that of panel data contemplating a manually collected database of 154 companies between 2010 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…With the results obtained by the present study, the hypothesis that the forecast error of the results is positively related to the risk rating on credit quality was confirmed. As it is a primitive study, no previous work was found on the relationship between forecast error and rating, however the research advances and connects the works of Gatsios (2013), Gatsios et al (2018), Jiang (2022), Lima et al (2016), Magnani et al (2022), andSaadaoui et al (2022).…”
Section: Final Considerationsmentioning
confidence: 98%
See 3 more Smart Citations
“…With the results obtained by the present study, the hypothesis that the forecast error of the results is positively related to the risk rating on credit quality was confirmed. As it is a primitive study, no previous work was found on the relationship between forecast error and rating, however the research advances and connects the works of Gatsios (2013), Gatsios et al (2018), Jiang (2022), Lima et al (2016), Magnani et al (2022), andSaadaoui et al (2022).…”
Section: Final Considerationsmentioning
confidence: 98%
“…Still on analysts' forecasts, Magnani et al (2022) evaluated the effects of hedging on analysts' forecasts. The authors concluded that in emerging markets, with high volatility of macroeconomic variables and political instability, the corporate hedging policy, the rating assigned to the credit ratings of public companies and liquidity indices are key variables that influence analysts' forecasts.…”
Section: Analysts' Forecasting Errormentioning
confidence: 99%
See 2 more Smart Citations